(untitled) ("Journal "U". Economy. Management. Finance.", 2020)
The purpose of this study is to identify the need to evaluate marketing activities through economic indicators. To achieve this goal, the author justified the relevance of the topic, considered the concept of efficiency, the indicators through which it is measured. The author also considered various methods for evaluating marketing activities. The conclusions formulated in the course of the study can be used in practice to measure the effectiveness of marketing activities.